Studies on Xin'an Medicine (新安医学) since the Ming and Qing Dynasties - Jian Wang; Yebo He (Wolters Kluwer Health/LWW, 2019)
This article reviews the studies on Xin'an medicine since the Ming and Qing dynasties and introduces the representative Xin'an physicians in different periods and their medical works as well as the efforts made by researchers and scholars in the 20th Century, aiming to interpret the historical values and impacts of Xin'an medicine and hence facilitate its development in future.